The Democratization of the Educational Administration in Argentina: A Comparison of Provincial Policies - Gorostiaga, Jorge M. (Education Policy Analysis Archives, 2007)
This article analyses some of the main school management reforms implemented at the provincial level from the mid-1980s in Argentina, and relates them to the national policies and to global trends regarding the governance of educational systems. It is argued that democratic and participatory proposals, which responded to a great extent to the return of the country to political democracy, began to give ground as the provinces focused on administrative rationalization and as the national government promoted a concept of school autonomy based on educational quality and efficiency criteria defined at the central level. On the other hand, participatory policies and programs faced various obstacles that originated in a context of social inequality, the prevailing institutional cultures, and the lack of a clear idea about the requirements and implications of implementing democratic practices at schools.